2022
DOI: 10.1088/1755-1315/974/1/012088
|View full text |Cite
|
Sign up to set email alerts
|

Superior morphological characteristics of Kobura promising Robusta coffee clones from South Sumatera Province

Abstract: Released new superior clones of Robusta coffee have an essential role as sources of high qualities planting materials. Each clone should have unique and distinctive morphological marker(s) which are easily visual-characterized. Assessment of morphological markers allows plant breeders to discriminate and identify the most promising genotypes for variety development. This study aimed to characterize morphological markers and reveal the superiority of 3 promising clones of Robusta coffee, i.e., Kobura 1, Kobura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Dalazen et al (2020) and Lemos et al (2020) found Fruity and Sweet descriptors in their highest quality Robusta clones. Promising Robusta genotypes from Sumatra were described by Sweet and Floral descriptors (Wicaksono et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Dalazen et al (2020) and Lemos et al (2020) found Fruity and Sweet descriptors in their highest quality Robusta clones. Promising Robusta genotypes from Sumatra were described by Sweet and Floral descriptors (Wicaksono et al, 2022).…”
Section: Discussionmentioning
confidence: 99%